2005
DOI: 10.1677/joe.1.06051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and pregnancy on the circulatory activin response of sheep to acute inflammatory challenge by lipopolysaccharide

Abstract: The release of activin A in response to intravenous injection of the bacterial cell-wall component lipopolysaccharide (LPS) was investigated in an ovine model of acute inflammatory challenge in newborn and adult sheep, and in non-pregnant and pregnant ewes. Neonatal lambs (<20 days of age) showed a quantitatively similar response in terms of circulating concentrations of activin A, its binding protein follistatin and the cytokine interleukin-6 compared with adult ewes challenged with an equivalent dose (300 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
(45 reference statements)
0
17
2
Order By: Relevance
“…data]. Transient fetal hypoxemia, acidemia, and maternal (and therefore, fetal) hyperthermia [22] have been recorded in response to LPS administration, and while it cannot be ruled out that any one or a combination of these could account for the changes, the fetal cerebellum has not hitherto been regarded as being particularly sensitive to these factors. Further work will be necessary to identify the processes that connect the inflammatory reactions in the uterus and placenta to the cells in the fetal brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…data]. Transient fetal hypoxemia, acidemia, and maternal (and therefore, fetal) hyperthermia [22] have been recorded in response to LPS administration, and while it cannot be ruled out that any one or a combination of these could account for the changes, the fetal cerebellum has not hitherto been regarded as being particularly sensitive to these factors. Further work will be necessary to identify the processes that connect the inflammatory reactions in the uterus and placenta to the cells in the fetal brain.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we administered LPS into the uterine artery (UTA) of pregnant sheep. As evidence suggests that LPS does not cross the ovine placenta [22] , we sought evidence for the hypothesis that fetal cerebellar damage can arise as a consequence of uteroplacental inflammation, rather than as a result of the direct effect of the endotoxin on the fetal brain.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, treatment with exogenous FS has confirmed the important requirement of the early release of activin A to regulate IL-1b, TNF-a and IL-6 secretion induced by LPS. 22,[32][33][34] Moreover, recent evidence has shown that macrophages are able to secrete activin A in response to the activation of TLR2, TLR4 and TLR9 (Figure 1 (1), right panel). [35][36][37][38][39] Accordingly, elevated activin A levels have been observed in a mouse model of endotoxemia and in patients with clinical sepsis condition.…”
Section: Monocytesmentioning
confidence: 93%
“…T cell-derived cytokines enhanced activin A secretion in monocytes and bone marrow stromal fibroblasts (38). Therefore, it appears that the activation-induced expression of activin A is most likely a common feature in immune (39,40). In Th cells, increased expression of activin A was found only in Th2 cells, but not in Th1 cells, indicating that activin A production is associated with Th2-type immune responses.…”
Section: Cd25mentioning
confidence: 96%